Damage modeling of basaltic rock subjected to cyclic temperature and uniaxial stress. (July 2015) - Zhou, S.W.; Xia, C.C.; Hu, Y.S.; Zhou, Y.; Zhang, P.Y.
Abstract: The deformation characteristics of basalt rocks subjected to cyclic uniaxial stress and cyclic temperature were investigated, and a corresponding damage model was established. Cyclic uniaxial stress–temperature tests were conducted in which stress upper limit was 80% or 65% of the uniaxial compressive strength and peak temperature was 60 °C or 90 °C. A damage model for rocks subjected to cyclic stress–temperature was proposed, which applied statistical damage mechanics and continuum damage mechanics. Cyclic stress–temperature tests exhibited superposition of cyclic stress and temperature effects. Basalt specimens were damaged gradually as the cycle number increased, and failed in cycles where maximum stress was 80% of the uniaxial compressive strength. However, the specimens hardened and did not fail when maximum stress was 65% of the uniaxial compressive strength and the highest temperature was 60 °C. The peak strain of damaged specimens underwent initial, steady, and acceleration stages; the Young׳s modulus decreased rapidly in the initial cycles, but the reduced rate decreased further in subsequent cycles. The peak and residual strains of hardened specimens decreased as the cycle number increased. However, the Young׳s modulus had an opposite trend; moreover, the higher the temperature, the less the Young׳s modulus increased. The proposed damage model can be degenerated into existing models or be regarded as an extension of them. Graphical abstract: Damage models to describe the effects of cyclic uniaxial stress and cyclic temperature were proposed on the basis of statistical damage mechanics. In a stress–temperature cycle, the total damage was regarded as superposition of the stress-induced damage and temperature-induced damage. The proposed models provided good fit to the laboratory data. Highlights: Cyclic uniaxial stress–temperature tests were performed on basalt specimens. Deformation characteristics of basalt rocks subjected to cyclic uniaxial stress and cyclic temperature was obtained. A damage model for rocks subjected only to cyclic temperature was proposed. Damage models for rocks subjected to cyclic uniaxial stress and cyclic temperature were proposed. The proposed models provided good fit to the laboratory data.